2008
DOI: 10.1577/1548-8446-33.9.433
|View full text |Cite
|
Sign up to set email alerts
|

Development of New Water Temperature Criteria to Protect Colorado's Fisheries

Abstract: Water temperature fundamentally influences aquatic diversity and ecosystem health. In Colorado, temperature water quality criteria were revised in January 2007 based on a rigorous evaluation of the thermal requirements of fish species resident in Colorado. This article presents an account of how this process was conducted, and details the resultant criteria. The purpose of developing these criteria was to protect coldwater and warmwater fishes, especially native species such as cutthroat trout (Oncorhynchus cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 17 publications
1
54
0
Order By: Relevance
“…The choice of the sublethal criterion can vary with the author: , for example, cite the onset of violent muscular spasms (Matthews and Maness, 1979), the loss of balance (Watenpaugh et al, 1985) or opening of the opercula (Middaugh et al, 1975). The boundary temperatures obtained with this type of experiment are often higher than those found with the ILT method, due to the generally shorter period of exposure to the tested temperatures (Todd et al, 2008).…”
Section: Determination Of Critical Temperaturesmentioning
confidence: 80%
See 1 more Smart Citation
“…The choice of the sublethal criterion can vary with the author: , for example, cite the onset of violent muscular spasms (Matthews and Maness, 1979), the loss of balance (Watenpaugh et al, 1985) or opening of the opercula (Middaugh et al, 1975). The boundary temperatures obtained with this type of experiment are often higher than those found with the ILT method, due to the generally shorter period of exposure to the tested temperatures (Todd et al, 2008).…”
Section: Determination Of Critical Temperaturesmentioning
confidence: 80%
“…Different thermal variables (adapted from Beitinger et al, 2000b;Todd et al, 2008). (a) Different temperature variables versus acclimatation temperature, (b) synthetic range of temperature tolerance.…”
Section: Figurementioning
confidence: 99%
“…Variation in annual flow regime, particularly summer low flows, may represent a population bottleneck for nonmigratory fishes (Courter et al 2009). Larger residents require more space and tend to occupy faster and deeper water than smaller individuals, and streams that do not maintain sufficient flow are unlikely to support large, old, resident O. mykiss (Todd et al 2008). As an example, by manipulating stream flow, Harvey et al (2006) found that growth rates of O. mykiss were 8.5 times lower in reaches with reduced flow than in control reaches.…”
Section: Stream Flowmentioning
confidence: 99%
“…6; Pavlov et al 2001a. Indeed, such features (e.g., depth, food, temperature) were found to be important to the maintenance of residents in studies of other areas and populations (Bentley et al 2012;McMillan et al 2012;Todd et al 2008).…”
Section: Stream Geomorphology and The Role Of Lakesmentioning
confidence: 99%
“…Since temperature was inversely related to stream altitude in our study sites (r = -0.87; p < 0.01) we concur that this could be a relevant factor for excluding brook trout from sympatric distribution at high stream altitudes (Fausch, 1988). However we contend that temperature was probably not the unique limiting factor to account for salmonids segregation during the sampling period, since S. fontinalis and O. mykiss exhibit similar chronic and acute temperature (Todd et al, 2008). Larson & Moore (1985) noted that sympatry between both species was also related to stream length and Clark & Rose (1997) concluded that rainbow trout dominance over brook trout in Appalachian streams was related to factors such fecundity and year class failures.…”
Section: Discussionmentioning
confidence: 94%